Mobilier d'Art - Cutero, Hilton Cedrick Lumba (Animo Repository, 2021)
The Furnisher Corp., established in September 2018, is a wholesale and retail company engaged in furniture products. It operates a 107-square meter furniture retail store under the trade name Mobilier d’Art in SM City Telabastagan. The company currently has three full-time employees: a supervisor and two sales assistants. Hilton serves as the chief executive and manager, and makes all business decisions for the company. Mobilier d’Art has been operating for more than two years. The company barely managed to break-even and was troubled by its profit rate of -1% in 2019. The company observed and identified the primary causes of the problem, namely, high rent, small market, and small showroom. The Furnisher Corp. exhausted the most feasible options to improve its profitability. Initially, the company targeted upper-income customers and offered luxurious furniture products such as chinoiseries, contemporary Italian chairs, Chippendale beds, and contemporary cabinets. Unfortunately, no substantial target market was observed in the first month of operation. The company pivoted marketing strategies to cater the actual market and satisfy customer needs. The company also successfully bargained with the mall administration regarding rent and free exhibit areas since September 2019. The company partnered with the family business Easy Home Furniture Center to cut operating costs. Furthermore, a cross-functional skeleton workforce was implemented to further reduce operating costs. The marketing pivot significantly improved the company’s revenue. Gross monthly revenue increased 135% compared with the first month of operation. The company was able to survive in the succeeding months. The simultaneous implementation of strategies was able to cut operating costs, and hence profitability. In two years, the company was able to repay more than 80% of its interest-free business loan. Several financial and strategic planning tools and frameworks were used to help discuss the developments in the business. The company’s projected and actual budgets were also analyzed to help explain the cause of variance throughout the business operation. The internal and external environments were studied using strategic planning tools to help understand how the management decided on its strategies. The 7S McKinsey Framework was adopted to help examine the changes from the intended to the current strategies in the key internal elements of the company, and explain how the different strategies affected the company. The Furnisher Corp. gained various experiences in the fields of business and management throughout its operation. With an uncertain future, the company is looking into exit or expansion strategies to limit losses and/or improve profitability.